Effects of different dietary energy and protein levels on the performance and carcass characteristics of native hilly chicken during growing phase in confinement - Khatun, Halima; Faruqe, Shakila; Mostafa, Md Golam (Asian-Australasian Journal of Bioscience and Biotechnology, 2021)
Two hundred and sixteen 10 weeks of age hilly chickens were used to determine the effects of dietary energy and protein level on growth performance, carcass characteristics and meat quality. The chicks were randomly allotted in to 3×3 factorial in a completely randomize design. Three levels of energy (2600, 2700 and 2800 ME kcal/kg) and three levels of dietary proteins (16, 17 and 18% CP) were offered ad libitum to the chicks from 10-16 weeks of age. There were no significant interaction effect between dietary protein and energy levels in the diets. At 10-16 weeks of age hilly chickens fed with the medium protein diet (17% CP) showed shortened feed intake (p<0.001) but FCR found better in 16% CP diet. Dietary protein levels higher than 16% CP did not show any significant effect on growth performance. However hilly chicken fed with lower protein diet converted protein to body weight and body weight gain more efficiently than those fed higher protein diets. Dietary energy contents of 2600, 2700 and 2800 ME kcal/kg did not affect the growth performance of hilly chicken except ME, CP intake and protein conversion ratio. ME and CP intake was increased with increasing dietary ME and CP levels (p<0.000). Protein utilization was better (p<0.05) in higher (2800 ME kcal/kg) and medium (2700 ME kcal/kg) ME level diet. L*, a* and b* of breast meat was not affected by dietary ME and CP (p>0.05). Dietary energy and protein level did not significantly (p>0.05) affect the drip loss, cooking loss and pH of breast meat between the treatments. Based on the data of growth performance, carcass characteristics and meat quality, the optimal dietary ME requirement of hilly chicken from 10-16 weeks of age is 2800 ME kcal/kg and the CP requirement is 16%. Asian Australas. J. Biosci. Biotechnol. 2021, 6 (1), 1-9